Opportunities for future research and innovation on food and nutrition security and agriculture - The IAP ‘s global perspective - von Braun, Joachim (2019)
Joachim von Braun POLICY SEMINAR Transforming Food Systems to Deliver Healthy, Sustainable Diets : The View from the World’s Science Academies Co-Organized by IFPRI and InterAcademy Partnership FEB 14, 2019 - 12:15 PM TO 01:45 PM EST